Comparative nutritional composition of selected grain sorghum varieties - G. Goldy; T. Walters; Andrew William Lenssen; Jack G. Riley; Gerry L. Posler (Kansas Agricultural Experiment Station Research Reports, 1986)
For the 188 grain sorghum varieties studied, in vitro digestibilites were statistically similar, but there was a significant difference between the 12 production locations. Crude protein, calcium, and phosphorus levels indicated slight varietal differences; however, strong locational effects were evident.
Keywords: Cattlemen' s Day; 1986; Kansas Agricultural Experiment Station contribution; no. 86-320-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 494; Beef; Grain sorghum; Digestibilities